Medievalia et Humanistica, No. 49 (Bloomsbury Publishing (US), 2026)
Since its founding in 1943, Medievalia et Humanistica has won worldwide recognition as the first scholarly publication in America to devote itself entirely to medieval and Renaissance studies. Since 1970, a new series, sponsored by the Modern Language Association of America and edited by an international board of distinguished scholars and critics, has published interdisciplinary articles. In yearly hardcover volumes, the new series publishes significant scholarship, criticism, and reviews treating all facets of medieval and Renaissance culture: history, art, literature, music, science, law, economics, and philosophy. This open access book contains four articles ranging from medieval literature (discovery of the Self in the twelfth century) and philosophy (reception of Moses Maimonides in Latin) to Humanist poetry (Boccaccio on leisure) and panegyrics (Nagonio on Henry VII and Prince Arthur, with an appendix containing a couple of poems hitherto unedited, along with an English translation). In addition, there are five book reviews which cover various epochs, genres, and discourses. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.